2020
DOI: 10.1002/pbc.28793
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline as a biomarker of bacteraemia during induction treatment for childhood acute lymphoblastic leukaemia

Abstract: Background: Systemic infections are a major cause of morbidity in children with acute lymphoblastic leukaemia (ALL). However, identification of patients at increased risk is still a challenge. Knowing that both neutropaenia and gastrointestinal toxicity are risk factors for bacteraemia, we aimed at comparing absolute neutrophil counts (ANC) and plasma citrulline levels (indicating enterocyte loss) in children with ALL with and without bacteraemia during induction treatment. Procedure: We prospectively included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Interestingly, these metabolites showed inverse correlations with CRP, a marker of systemic inflammation suggesting that the levels of some of these metabolites increase in parallel with attenuation of CRP levels by JAK inhibition. Some reports also found low levels of arginine and citrulline in severe infectious and inflammatory states associated with elevated CRP release ( 89 , 90 ).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, these metabolites showed inverse correlations with CRP, a marker of systemic inflammation suggesting that the levels of some of these metabolites increase in parallel with attenuation of CRP levels by JAK inhibition. Some reports also found low levels of arginine and citrulline in severe infectious and inflammatory states associated with elevated CRP release ( 89 , 90 ).…”
Section: Discussionmentioning
confidence: 98%
“…wDuring induction treatment, 27 of 106 patients (25%) were diagnosed with BSI, with median debut day 12 4–29 (Figure 1). Two of 106 patients (2%) had polymicrobial BSI episodes.…”
Section: Resultsmentioning
confidence: 99%
“…The study was approved by the local ethics committee and conducted in accordance with the Declaration of Helsinki and written and oral informed consent was obtained from all patients or legal guardians. Clinical characteristics are listed in Table 1, and additional research data from a subgroup of this patient cohort has been reported previously 25–27 …”
Section: Methodsmentioning
confidence: 99%
“…Plasma citrulline is produced by enterocytes [ 38 ]. Lower levels of citrulline correspond to cell loss and thus to tissue damage and inflammation [ 72 ]. Mucositis was also introduced as marker for an increased risk of bacteremia in ALL [ 72 ].…”
Section: Microbiome In Allmentioning
confidence: 99%
“…Lower levels of citrulline correspond to cell loss and thus to tissue damage and inflammation [ 72 ]. Mucositis was also introduced as marker for an increased risk of bacteremia in ALL [ 72 ]. Furthermore, plasma C-reactive protein level acts as an indicator for inflammation, and its direct increase at sites of infection was also correlated with the increase in specific bacteria at different therapy time points [ 38 ].…”
Section: Microbiome In Allmentioning
confidence: 99%